Pemahaman Wirausaha Bagi Remaja dan Ibu-Ibu Majlis Taklim Al-Muslimah Kelurahan Tembesi Kota Batam - Ibrahim, Ukas; Jamba, Padrisan; Husda, Anggun Permata (ASOSIASI IDEBAHASA KEPRI, 2024)
The material provided in this coaching is divided into 2 groups, namely the legal group and the business group aimed at